2009
DOI: 10.1172/jci34862
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular type 1 angiotensin receptors augment kidney injury and inflammation in murine autoimmune nephritis

Abstract: Studies in humans and animal models indicate a key contribution of angiotensin II to the pathogenesis of glomerular diseases. To examine the role of type 1 angiotensin (AT 1 ) receptors in glomerular inflammation associated with autoimmune disease, we generated MRL-Fas lpr/lpr (lpr) mice lacking the major murine type 1 angiotensin receptor (AT 1A ); lpr mice develop a generalized autoimmune disease with glomerulonephritis that resembles SLE. Surprisingly, AT 1A deficiency was not protective against disease but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 75 publications
4
69
0
Order By: Relevance
“…30 Activated AT1 signaling at podocytes would be sufficient to cause proteinuria and glomerular injury. 31,32 Furthermore, the crosstalk between AngII and GC-A signaling was shown in cultured podocytes. 33 These data suggest that lack of GC-A in the kidney should have a critical role in exaggerated activation of the "local" RAAS, which was abrogated by ARB treatment.…”
Section: Discussionmentioning
confidence: 99%
“…30 Activated AT1 signaling at podocytes would be sufficient to cause proteinuria and glomerular injury. 31,32 Furthermore, the crosstalk between AngII and GC-A signaling was shown in cultured podocytes. 33 These data suggest that lack of GC-A in the kidney should have a critical role in exaggerated activation of the "local" RAAS, which was abrogated by ARB treatment.…”
Section: Discussionmentioning
confidence: 99%
“…29 We chose AT 1a R-deficient mice, so the AT 1b R-blocking action of losartan may have antiinflammatory effects. Crowley et al 30 showed previously that AT 1b receptor activation increased podocyte injury and expression of inflammatory mediators using AT 1a R-deficient lpr mice. Also, administration of losartan reduced markers of kidney disease, such as proteinuria, glomerular pathology, and inflammatory cytokine expression.…”
Section: Kusunoki Et Al Telmisartan Protects Kidney Via Ppar␥/hgf Patmentioning
confidence: 96%
“…However, a small number of human trials are ongoing or at early stages, mainly focused on retarding or preventing diabetic nephropathy. The original clinical trials that used angiotensin converting enzyme inhibitors (ACEI) or angiotensin receptor antagonists (12) were designed to lower blood pressure and glomerular hyperfiltration, although newer evidence suggests that a major role for the angiotensin receptor, which is widely expressed by the kidney vasculature, perivascular cells, epithelium, and inflammatory leukocytes, is to stimulate inflammatory pathways (18). It is likely therefore that current use of ACEI and angiotensin receptor inhibitors to treat kidney disease is effective at least in part by blocking proinflammatory and profibrotic pathways (7).…”
Section: Clinical Trials In Fibrogenesismentioning
confidence: 99%